Analysis of Stop Codons within Prokaryotic Protein-Coding Genes Suggests Frequent Readthrough Events - Belinky, Frida; Ganguly, Ishan; Poliakov, Eugenia; Yurchenko, Vyacheslav; Rogozin, Igor B (International journal of molecular sciences, 2021)
Nonsense mutations turn a coding (sense) codon into an in-frame stop codon that is assumed to result in a truncated protein product. Thus, nonsense substitutions are the hallmark of pseudogenes and are used to identify them. Here we show that in-frame stop codons within bacterial protein-coding genes are widespread. Their evolutionary conservation suggests that many of them are not pseudogenes, since they maintain dN/dS values (ratios of substitution rates at non-synonymous and synonymous sites) significantly lower than 1 (this is a signature of purifying selection in protein-coding regions). We also found that double substitutions in codons-where an intermediate step is a nonsense substitution-show a higher rate of evolution compared to null models, indicating that a stop codon was introduced and then changed back to sense via positive selection. This further supports the notion that nonsense substitutions in bacteria are relatively common and do not necessarily cause pseudogenization. In-frame stop codons may be an important mechanism of regulation: Such codons are likely to cause a substantial decrease of protein expression levels.
Keywords: Pseudogenes; otevřené čtecí rámce; terminační kodon; Base Sequence; prokaryotické buňky; Codon, Nonsense; bakteriální proteiny; modely genetické; Bacterial Proteins; selekce (genetika); in-fame stop codon; Evolution, Molecular; molekulární evoluce; Selection, Genetic; nesmyslný kodon; Phylogeny; Models, Genetic; Point Mutation; Bacteria; sekvenční homologie nukleových kyselin; population polymorphism; Sequence Homology, Nucleic Acid; bodová mutace; sekvence nukleotidů; Codon, Terminator; negative selection; short-term evolution; Open Reading Frames; expression; fylogeneze; Prokaryotic Cells; pseudogeny